Implementation of Artificial Intelligence Technology as a Learning Means for Students at SMAN 2 Monta Bima - Nurfidari; Ahyar, Ahyar; Ita Fitriati (Expert Net: Exploration Journal of Technological Education Trends, 2024)
With the rapid and significant development of the times, many software and sites have emerged in the form of websites based on AI (Artificial Intelligence), one of which is Chatgpt and Perplexity AI, which are commonly known as artificial intelligence that can help with assignments and teaching materials. , according to human desires and needs in a short time, depending on how the user describes the prompt to the AI. AI can also be useful and can be implemented in the world of education, in schools it can increase students' understanding of Artificial Intelligence (AI) through the use of AI tools. This research aims to implement Artificial Intelligence technology as a learning tool, and it is hoped that students will be able to use AI, especially to support the learning of class Intelligence), and Data Analysis. With sampling with a total of 13 students and 1 teacher. The results of the research are that students understand and are able to operate several AI (Artificial Intelligence) tools, one example is Chatgpt and Perplexity AI, and understand how to utilize their respective Android systems. With this, students become active during the teaching and learning process, especially when collecting school assignments.   ABSTRAK Dengan perkembangan zaman yang sangat pesat dan cukup signifikan, sudah banyak bermunculan  software maupun situs dalam bentuk  website yang berbasis AI (Artificial intellegence), salah satunya adalah Chatgpt dan perplexity AI, yang biasa di kenal sebagai  kecerdasan buatan yang dapat membantu mengerjakan tugas maupun bahan ajar, sesuai dengan keinginan dan kebutuhan manusia dalam waktu yang singkat, tergantung bagaimana user mendeskipsikan promp pada AI. AI juga bisa bermanfaat dan dapat diimplementasikan pada dunia pendidikan, di sekolah dapat meningkatkan Pemahaman Siswa tentang Artificial Intelligence (AI) melalui Penggunaan Tools AI. Penelitian ini bertujuan untuk mengimpelmentasikan teknologi Artificiall Intelegence sebagai sarana belajar, dan diharapkan siswa dapat menggunakan AI, utamanya untuk mendukung pembelajaran siswa kelas X SMAN 2 Monta, Metode penelitian yang di gunakan  adalah metode kualitatif, dengan cara observasi, pengumpulan data, impelementasi AI (Artificial Intelegence), dan Analisis data. Dengan sampling dengan jumlah  13 siswa dan 1 orang guru. Hasil penelitian siswa paham dan mampu mengoperasikan beberapa tools AI (Artificiall Intelegence), salah satu contohnya adalah Chatgpt dan Perplexity AI, Dan paham dalam memanfaatkan sistem Android-nya masing-masing. Dengan ini siswa menjadi aktif ketika proses belajar-mengajar, lebih-lebih ketika mengumpulkan tugas sekolah.